Pelatihan Akuntansi Dasar dalam Penyusunan Laporan Keuangan pada Usaha Mikro, Kecil, dan Menengah di Aceh Tamiang - Risuhendi R; Firman Syarif; Muhammad Simba Sembiring; Sisi Maghfirah Rahmah Sembiring (Jurnal Pengabdian kepada Masyarakat Indonesia (JPKMI), 2025)
This community service activity aims to improve financial literacy and basic accounting skills for Micro, Small and Medium Enterprises (MSMEs) in Aceh Tamiang Regency. The results of the identification show that most MSMEs still face obstacles in recording and preparing financial reports that meet standards, thereby hampering access to financing and effective decision-making. The activity was carried out through basic accounting training covering transaction recording, profit and loss statement preparation, capital changes, and balance sheets. The implementation methods included seminars, report preparation simulations, and individual mentoring. Participants came from various sectors, such as culinary, handicrafts, services, and trade, spread across the sub-districts of Rantau, Karang Baru, Manyak Payed, and Kota Kuala Simpang. The results of the activity showed a significant increase in participants' understanding and skills, as seen from the pre-test and post-test results and their ability to prepare financial reports more systematically. This activity is expected to improve business management efficiency, expand access to financing, and strengthen the competitiveness of MSMEs in Aceh Tamiang. More broadly, this programme contributes to the achievement of sustainable development goals (SDGs), particularly in poverty reduction and inclusive economic growth.